Microstructural features induced during compression of Al-18Si-2.5Cu-0.6Fe alloy at elevated temperature - Khemraj; Jha A.K.; Ojha S.N. (My University, 2025)
The research objective of the present paper is to study the feasibility of bulk processing of Al-18Si-2.5Cu-0.6Fe alloy. The microstructural features induced during high-speed compression of alloy under different processing conditions have been investigated and reported. The compression of cylindrical test specimens between the top and bottom impression dies and also through a converging die at elevated temperatures has been considered for the study. Experiments have been performed with different aspect and reduction ratios for impression and converging die compression respectively. The results reveal that considerable refinement in the microstructure of the compressed alloy occurred and is more significant in converging die compression at elevated temperature. The development of microstructural features during hot compression of the alloy at different processing conditions was also discussed. The results of the present study provide a valuable insight to understand the microstructural refinement during high-speed compression at elevated temperatures. Copyright © 2017 Inderscience Enterprises Ltd.